N-(3,4-Dichlorophenyl)-2,4-dimethylbenzenesulfonamide - Gowda, B. Thimme (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(14)H(13)Cl(2)NO(2)S, the configurations of the N—C bond with respect to the S=O bonds are trans and gauche. The molecule is bent at the S atom with a C—SO(2)—NH—C torsion angle of −69.7 (2)°. The conformation of the N—H bond is syn to the 3-chloro group in the substituted aniline ring. The two benzene rings are tilted with respect to each other by 82.4 (1)°. The presence of N—H⋯O(S) hydrogen bonding packs the molecules into supramolecular chains along the b axis.